APPLICATION OF QUANTUM TEACHING LEARNING MODEL AS AN EFFORT TO IMPROVE STUDENT LEARNING OUTCOMES - Annasari Siregar (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
Low student learning outcomes are a problem in schools, including where researchers teach. As an effort to improve student learning outcomes is the application of the quantum teaching learning model. This research was conducted on fifth grade students of SDN 022 Bathin Solapan with a total of 35 students. This research is a classroom action research. The instrument used was a learning outcome test. The results of this study found that the average initial data of students was 59.71 with 11 students who completed, in the first cycle, there was an increase with the average student learning outcomes being 68.14 with 23 students who achieved mastery, in cycle II student learning outcomes have reached the expected success indicators, namely the average student learning outcomes amounted to 75.28 with 32 students who were able to achieve the minimum passing criteria. The conclusion that can be drawn is that the application of the quantum teaching learning model can improve student learning outcomes